Vestibular assessment in occupational noise-induced hearing loss - Naema M Ismail; Reda M.A.A Behairy; Dalia H Galhom; Shimaa A.E.A.A. E.A Metwally (Wolters Kluwer Medknow Publications, 2021)
Background Occupational noise can cause hearing loss and also may affect the vestibular system and result in vestibular dysfunction. Aim To study the effect of noise exposure on the cervical vestibular-evoked myogenic potential (cVEMP) and ocular vestibular-evoked myogenic potential (oVEMP) and to correlate between duration of noise exposure and vestibular dysfunction if present. Patients and methods A total of 60 patients were included in this study, comprising a study group of 30 patients with noise-induced hearing loss and a control group of 30 healthy participants with normal hearing and vestibular function. Patients of both groups underwent cVEMP and oVEMP. Results cVEMPs showed a highly statistically significant difference between the study and control groups regarding P13 and N23 latencies and P13-N23 amplitude, and oVEMPs showed a statistically significant difference between the study and control groups regarding N1 and P1 in latencies and N1-P1 amplitude. A positive correlation was found between duration of noise exposure and VEMPs latencies, whereas a negative correlation between it and VEMPs amplitude. Conclusion Noise exposure is a hazard to inner ear structures that can enhance the damage of vestibular part, especially the sacculocolic pathway.